REPRESENTASI MEDIA BERDASARKAN GENDER PADA KARAKTER SERIAL ANIMASI “AVATAR: THE LAST AIRBENDER” - Ramadhina, Az-zahra Mutiara Syofi; Wibowo, Kunto Adi; Rahmawan, Detta (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. This research was conducted to see how the media presents characters in animated series based on gender roles. The animated series chosen was